Periodic behaviours emergent in discrete systems with random dynamics - Pickton, John-Nathan Edward (2017)
Periodic behaviours in continuous media can be described with great power and economy using conceptual machinery such as the notion of a field. However periodic effects can also be `observed' in collections of discrete objects, be they individuals sending emails, fire-flies signalling to attract mates, synapses firing in the brain or photons emerging from a cavity. The origin of periodic behaviours becomes more difficult to identify and interpret in these instances; particularly for systems whose individual components are fundamentally stochastic and memoryless. This thesis describes how periodic behaviour can emerge from intrinsic fluctuations in a fully discrete system that is completely isolated from any external coherent forcing.